Advancement in management of epidermolysis bullosa. Issue 4 (August 2016) - Cohn, Heather I.; Teng, Joyce M.C.
Abstract : Purpose of review: Epidermolysis bullosa is a hereditary skin disorder characterized by skin fragility. However, the disease can manifest in many different organ systems, therefore children born with epidermolysis bullosa may have life long, complex medical needs. In this review, we will use a system-based approach to highlight important aspects of disease management and recent advancements in each of the areas. In addition, we will overview some of the cutting edge therapeutic developments in epidermolysis bullosa. Recent findings: Recent advancements in supportive care of epidermolysis bullosa with focus on wound, pain, pruritus and nutrition status were discussed. Clinical surveillance and complication prevention are critical to improve clinical outcomes. Generalized epidermolysis bullosa is a systemic disease with increased morbidity and mortality; therefore, complex care using a multidisciplinary approach will provide the greatest benefits for patients. Current targeted treatments for epidermolysis bullosa aim at restoring the skin integrity using protein, cell, and gene therapies. Summary: Improvement in care of epidermolysis bullosa in recent years results from keen clinical observation, novel molecular targeting, and the embracement of translational research.